2002
DOI: 10.1523/jneurosci.22-03-01010.2002
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT3Subtype of Serotonin Receptor Contributes to Nociceptive Processing via a Novel Subset of Myelinated and Unmyelinated Nociceptors

Abstract: Serotonin is a major component of the inflammatory chemical milieu and contributes to the pain of tissue injury via an action on multiple receptor subtypes. Here we studied mice after genetic or pharmacological disruption of the 5-HT 3 receptor, an excitatory serotonin-gated ion channel. We demonstrate that tissue injury-induced persistent, but not acute, nociception is significantly reduced after functional elimination of this receptor subtype. Specifically, in the setting of tissue injury, the 5-HT 3 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
207
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 342 publications
(235 citation statements)
references
References 41 publications
20
207
0
8
Order By: Relevance
“…Table 1 is a large, but certainly not comprehensive list of antinociceptive targets. For example, 5HT 3 and other receptors in the spinal cord are capable of nociceptive modulation (Zeitz et al, 2002). However, mapping studies have shown that improgan acts in the brain stem, but not in the spinal cord (Nalwalk et al, 2004), making many of these receptors unlikely targets for CC12.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 is a large, but certainly not comprehensive list of antinociceptive targets. For example, 5HT 3 and other receptors in the spinal cord are capable of nociceptive modulation (Zeitz et al, 2002). However, mapping studies have shown that improgan acts in the brain stem, but not in the spinal cord (Nalwalk et al, 2004), making many of these receptors unlikely targets for CC12.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known, however, if the effects of 5-HT 3 antagonists on alcohol drinking are mediated by this subunit or other(s), which may coexpress with the 3A subunit (eg, Fletcher and Barnes, 1998). To address this question, we examined alcohol drinking by mutant mice lacking the 5-HT 3A receptor subunit (Zeitz et al, 2002a). One of the primary findings of this study is that 5-HT 3A -null mice did not differ from wildtype controls on measures of voluntary alcohol drinking either during or after a sucrose fading initiation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Mice 5-HT 3A receptor-null mice were derived by homologous recombination as previously reported (Zeitz et al, 2002a). F1 hybrid C57BL/6J Â 129vJ heterozygous progeny were backcrossed to C57BL/6J mice to produce F9 generation congenics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations